Effect of Root-Nodule Bacteria on Growth of Acacia Saligna Under Salt Stress - Mohamed, Omran Ali (Al-Mukhtar Journal of Sciences, 2018)
The Pot experiment was conducted at Lath-house to study the effect of Root-nodules bacteria on growth of Acacia saligna under different levels of salt stress 4،5،8،10 dsm-1 .With four root-nodule bacteria strains NA1، NA2 ، NA3 ، NA4and without inoculation NA0 . The results showed that the inoculationof different strains of the root bacterium significantly reduced the harmful effects of saline.The inoculated plants in their ability to tolerate different concentrations of salinity. Results indicated that the strain NA4 was superior to the rest of the strains in all studied traits، NA1، NA2 ، NA3 . The high levels had significant differences compared to the lowest level of salinity 4 dsm-1 where this level exceeds the other concentrations in all studied traits، ( number of root nodes formed for each plant، the dry weight of root-nodule ، dry weight of vegetative total، concentration of nitrogen in soil) . The interference transactions between the Rhizobium strains and the levels of salinity 4 dsm-1 was more significant than that of the other levels of salinity in all studied traits.